What Collaboration Means to Me: How We Do Don't Collaborate at The Library Collective - Halaychik, Corey; Maynor, Ashley (Collaborative librarianship, 2018)
The Library Collective is a non-profit organization devoted to redefining the library professional development landscape by providing low-cost, high-value learning opportunities for librarians. At the heart of The Library Collective's efforts is a unique style of collaboration. The following column outlines how the Co-Founders and Co-Directors use and don't use collaboration to create a professional development environment that embraces creativity, celebrates failure, and doesn't cost a fortune.